2020
DOI: 10.1038/s41598-020-61268-9
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning attenuates kidney and heart injury in rats following transient suprarenal occlusion of the abdominal aorta

Abstract: Suprarenal aortic clamping during abdominal aortic aneurysm (AAA) repair results in ischemiareperfusion injury (IRI) in local (i.e. kidney) and distant (i.e. heart) tissue. To investigate perioperative approaches that mitigate IRI-induced tissue damage, Wistar rats underwent suprarenal aortic clamping either alone or in combination with short cycles of ischemic conditioning before and/or after clamping. Serum analysis revealed significant reduction in key biochemical parameters reflecting decreased tissue dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Studies have found that inflammatory cytokines directly released from site of injury can induce injury in distant organs [ 8 ]. In this study, we analyzed proinflammatory factors iNOS, TNF- α , IL-1 β , and IL-6, and anti-inflammatory factors Arg-1, TGF- β 1, IL-4, and IL-10 levels in the serum, hippocampus, and left ventricle at 24 hr after reperfusion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have found that inflammatory cytokines directly released from site of injury can induce injury in distant organs [ 8 ]. In this study, we analyzed proinflammatory factors iNOS, TNF- α , IL-1 β , and IL-6, and anti-inflammatory factors Arg-1, TGF- β 1, IL-4, and IL-10 levels in the serum, hippocampus, and left ventricle at 24 hr after reperfusion.…”
Section: Resultsmentioning
confidence: 99%
“…Heart. Free radical production is a critical player in tissue destruction caused by reperfusion injury [8]. To determine whether AAO can cause oxidative stress induced by I/R, ROS production was assessed.…”
Section: The Effect Of Aao On Ros Production In Brain Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The escape‐from‐senescence phenomenon could also be a mechanism contributing to this outcome (see the next section). Ever since GL13 discovery, the spectrum of pathological entities has been expanded to include benign, preneoplastic, and neoplastic lesions, while senescent cells have also been recognised in various experimental and ageing contexts (Table 2) [37,106,107,110–137]. In particular, in clinical settings, skin pathologies (nevi, seborrheic, and actinic keratoses), lung, pancreatic, urothelial and laryngeal precancerous lesions, various types of carcinomas following treatment, sarcomas, haematological malignancies (Langerhans histiocytosis), and a variety of tissues from aged organs were included (Table 2).…”
Section: Detecting Senescence Escape: a Challenging Taskmentioning
confidence: 99%